CLASSROOM OBSERVATIONS: TECHNOLOGY-BASED TEACHING PRACTICES - Laylo Turdiboyeva,; Eshdavlatova Adiba Zafarovna, (TADQIQOTLAR, 2026)
Abstract This study examines technology-based teaching through classroom observations, highlighting how digital tools enhance engagement, interaction, and participation. It finds  that  multimedia,  online  platforms,  and  assessments  support  learner-centered environments and motivation. Effective integration depends on teachers’ skills and alignment  with  objectives,  improving  instructional  quality  and  creating  more meaningful, responsive learning experiences.